IMPACT OF CULTURAL DIVERSITY & POLITICS ON TERRORISM AND FARMERS/HERDERS CLASH IN NIGERIA ( (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This paper is an analysis of the trend of insurgent attacks in Nigeria by the Boko Haram terrorist group and the Fulani extremists. The two groups were used as case studies because their modus operandi is quite similar. The information that formed the basis of this presentation is completely doctrinal as sourced from academic textbooks, journals, and online news publications. The research found that thousands of fatalities have been recorded as a result of the incessant attacks by the two groups. Going forward, it established the historical perspective that led to the emergence of the groups with emphasis on the attacks perpetrated by the groups from 2014 to 2018. Recommendations were made based on the outcome of the research to aid policymakers in making effective policies for the security and safety of all Nigerians.